Knowledge Management Implementation and Human Resource Development on Employee Performance - Ahmad Firman (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study aims to test and analyze the effect of the application of knowledge management and human resource development on the performance of employees of the Audit Board of the Republic of Indonesia, South Sulawesi Province. The population in this study was employees at the Audit Board of the Republic of Indonesia, South Sulawesi Province, which numbered 90 people. Sampling in this study used purposive sampling techniques, so the researchers determined 50 employees as samples. The source of this research data is primary data, which is data obtained from the results of distributing questionnaires to all respondents. The statistical method used to test hypotheses is logistic regression analysis. The results of the study based on the results of the analysis with the logistic regression method show that knowledge management and human resource development affect employee performance and the results of the Wald Test and Odds Ratio (EXP(B)) state that the application of knowledge management has a significant effect on employee performance